Investigating constraint-based reasoning for university timetabling problem - Ho, Irene Sheau Fen (Int Assoc Engineers-Iaeng, 2008)
University Course Timetabling Problems (UCTP) are a NP-complete, real-world problems, with many soft and hard constraints involved. The difficulties in generating a good timetable solution are different in almost every institution. This paper investigates the constraint-based reasoning algorithm to solve this complex UCTP. The approach used constraints-based reasoning to search for the best preference value base on the student capacity for each lecture. The proposed algorithm has been tested using a real world data from Faculty of Computer Science and Information System, University of Technology Malaysia and Faculty of Science at Ibb University - Yemen.